Geospatial epidemiology of leprosy in northwest Bangladesh: a 20-year retrospective observational study - Bulstra, Caroline A.; Blok, David J.; Alam, Khorshed; Butlin, C. Ruth; Roy, Johan Chandra; Bowers, Bob; Nicholls, Peter; de Vlas, Sake J.; Richardus, Jan Hendrik (Infectious diseases of poverty, 2021)
Leprosy is known to be unevenly distributed between and within countries. High risk areas or ‘hotspots’ are potential targets for preventive interventions, but the underlying epidemiologic mechanisms that enable hotspots to emerge, are not yet fully understood. In this study, we identified and characterized leprosy hotspots in Bangladesh, a country with one of the highest leprosy endemicity levels globally.
Gesehen am 21.07.2021